Polsko-radziecki traktat pokojowy zawarty w Rydze w 1921 r. (aspekty polityczno-narodowościowe) - Goclon, Jacek (Przegląd Nauk Historycznych, 2009)
The peace treaty signed in capital of Latvia on 18 March 1921 between Poland and Soviet Russia ended an armed conflict taking place between 1919 and 1920. In the treaty both sides agreed to guarantee mutual rights regarding language, culture and religion for the Russian and Ukrainian minorities on the western side of the border as well as for the Polish minority on the eastern side of the border. Russia and Ukraine committed themselves to give back all Polish works of art, museum collections, libraries and archives acquired from the territories of the Republic of Poland after 1772. Moreover, Poland was supposed to receive a monetary compensation of 30 million roubles for its economic input into the Russian Empire during the times of the Partition of Poland and also to regain industrial and railway equipment 29 million roubles worth. Nonetheless, the Russians did not meet the great majority of these obligations. The state border established in Riga put Poland in the direct neighbourhood with Latvia in the north and Romania in the south, thus isolating Soviet Russia from Germany, Hungary and Czechoslovakia. These territorial changes made Poland a "cordon" country against Bolshevik Russia and increased its geopolitical importance in this part of Europe. The Treaty of Riga changed radically the political structure of Europe and significantly complemented the Treaty of Versailles. which would have remained a dead letter in its numerous decisions without ultimate settlements between Poland and Soviet Russia. But this does not change the fact that the Treaty of Riga divided the Belorussian and Ukrainian nations into two parts: one remaining under the Polish administration and the second - doomed to repressions and national degeneration in Bolshevik totalitarianism (including over one million Poles). Weakness of the Ukrainian (and especially Belorussian) national movement in no case should have been an excuse for Poland to abandon its allies. Despite the war triumph of the Polish army. the Treaty of Riga resolutions happened to be the Polish failure. The lands of the First Republic of Poland (between the Bug River and the border before 1772) were divided in a very unjust way. The majority of this territory remained under control of the defeated Bolshevik Russia whereas victorious Poland gained a significantly smaller area.